2021
DOI: 10.1007/s10712-020-09623-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Geophysical and Radar Interferometric Techniques to Monitor Land Deformation Associated with the Jazan Salt Diapir, Jazan city, Saudi Arabia

Abstract: Using integrated Interferometric Synthetic Aperture Radar (InSAR) datasets (Envisat: 2003–2009; Sentinel-1: 2014–2018), local gravity surveys, and passive seismic data, we investigated the environmental hazards associated with the rise of the Miocene Jazan salt diapir (JZD; ~ 2 km2) within Jazan city, Saudi Arabia, and identified areas at risk in its immediate surroundings. Our findings include (1) the JZD outcrop and its northern, southern and western bordering areas have been undergoing substantial uplift (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 92 publications
(112 reference statements)
1
8
0
Order By: Relevance
“…The analysis of XRD revealed the dominance of gypsum, anhydrite, and halite in the salt dome (Figure 3). The findings of the current study coincide with those of previous studies such as , Basyoni and Aref (2016), Abdelrahman et al (2021), andPankratz et al (2021). Notably, gypsum and halite salts are active participants in land subsidence and have caused severe damage to buildings in different areas in the world (Romanoff, 1957;Johnson, 2008a;Johnson, 2008b).…”
Section: Mineralogy Of the Salt Domesupporting
confidence: 91%
See 2 more Smart Citations
“…The analysis of XRD revealed the dominance of gypsum, anhydrite, and halite in the salt dome (Figure 3). The findings of the current study coincide with those of previous studies such as , Basyoni and Aref (2016), Abdelrahman et al (2021), andPankratz et al (2021). Notably, gypsum and halite salts are active participants in land subsidence and have caused severe damage to buildings in different areas in the world (Romanoff, 1957;Johnson, 2008a;Johnson, 2008b).…”
Section: Mineralogy Of the Salt Domesupporting
confidence: 91%
“…surrounding area. It forms rolling hilly terrain in the old city of Jizan (Pankratz et al, 2021). The salt dome is characterized by a thick evaporite succession at the bottom consisting of rock salt and gypsum.…”
Section: Area Of Study and Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…No study has been conducted to assess the role of salt diapirs on shoreline changes on Farahsan Island. A single study conducted on the evaluation of the salt-related land deformation in Jazan city diapir nearly 50 km east of Farahsan island by Pankratz et al 67 revealed large rates of land deformation in the Jazan diapir. The study showed a rise in diapir's elevation in the center up to 4.7 mm/year while subsiding the low-relief flats by − 7.5 mm/year.…”
Section: Discussionmentioning
confidence: 99%
“…The city of Jazan comprises 17 governates and 32 towns. Although these locations differ in heights and location, their demographic, agricultural, educational, cultural, housing, healthcare and environmental qualities are virtually same ( Abo-Elmagd et al, 2018 , Alsheikh et al, 2017 , Pankratz et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%